Gestational growth trajectories derived from a dynamic fetal–placental scaling law. Issue 159 (31st October 2019) - Baller, Daniel; Thomas, Diana M.; Cummiskey, Kevin; Bredlau, Carl; Schwartz, Nadav; Orzechowski, Kelly; Miller, Richard C.; Odibo, Anthony; Shah, Ruchit; Salafia, Carolyn M.
Abstract : Fetal trajectories characterizing growth rates in utero have relied primarily on goodness of fit rather than mechanistic properties exhibited in utero . Here, we use a validated fetal–placental allometric scaling law and a first principles differential equations model of placental volume growth to generate biologically meaningful fetal–placental growth curves. The growth curves form the foundation for understanding healthy versus at-risk fetal growth and for identifying the timing of key events in utero .